2016
DOI: 10.1007/s10549-016-3997-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of apoptotic circulating tumor cells (aCTC) in metastatic breast cancer

Abstract: Intact and aCTC are predictive of outcome in MBC. Apoptotic CTC counts ≥ 5/7.5 ml in conjunction with iCTC at baseline have an independent unfavorable prognostic impact on OS. Decreasing aCTC at ≥ 5/7.5 ml in serial enumeration is associated with favorable outcome. Therefore, separate enumeration of iCTC and aCTC is useful in tailoring systemic treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 26 publications
1
26
0
Order By: Relevance
“…Regarding the optimized aCTC cut-off, >50% reduction (n = <50% reduction (n = 49) showed a median PFS of 6 (5-10) vs. 3 (3-5) months (p = 0.0085) and a OS of 24 (17-34) vs. 10 (7-16) months (p < 0.0001). Regarding the optimized iCTC+aCTC >66.7% reduction (n = 57) vs. <66.7% reduction (n = 51) showed a median PFS of 6 (5-10) vs. months (p = 0.0063) and a median OS of 24 [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] vs. 10 (7-15) months (p = 0.0025). The impact of the optimized cut-offs on OS and PFS is shown in Figure 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the optimized aCTC cut-off, >50% reduction (n = <50% reduction (n = 49) showed a median PFS of 6 (5-10) vs. 3 (3-5) months (p = 0.0085) and a OS of 24 (17-34) vs. 10 (7-16) months (p < 0.0001). Regarding the optimized iCTC+aCTC >66.7% reduction (n = 57) vs. <66.7% reduction (n = 51) showed a median PFS of 6 (5-10) vs. months (p = 0.0063) and a median OS of 24 [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] vs. 10 (7-15) months (p = 0.0025). The impact of the optimized cut-offs on OS and PFS is shown in Figure 3.…”
Section: Resultsmentioning
confidence: 99%
“…The prognostic value of baseline CTC counts and kinetics of CTC number (CTC kinetics) in relation to systemic therapy has been demonstrated in recent studies [6,10,24]. Thus far, either a change in CTC status or a 25% reduction or increase as a cut-off point has been used to define a significant change in CTC counts, rendering them useful for studying the influence of CTC kinetics on breast cancer prognosis [6,7,13,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…For CTC identification, we used Cellsearch ® (Janssen Diagnostics, Raritan, NJ/Menarini Silicon Biosystems, Inc, Florence, Italy) technology following the standard operating procedures. Briefly, CTCs from two 7.5 ml CellSave tubes per visit were subjected to EpCAM-based ferrofluid selection, immunostaining, and image analysis, taking care to exclude apoptotic cells from CTC analysis in all samples [42,43]. One CellSave tube was used to identify patients with cytokeratin-positive (CK+), CD45-, and HER2-CTCs using phycoerythrin-conjugated antibodies recognizing epithelial cell-specific CKs (predominantly cytokeratins 8, 18, and 19), allophycocyanin (APC)-conjugated antibody directed against the white blood cell marker CD45, and 6-diamidino-2-phenylindole (DAPI) to stain nuclei.…”
Section: Ctc Enrichment Immunostaining and Image Analysismentioning
confidence: 99%
“…50 A recent study has shown that in metastatic breast cancer, intact and apoptotic CTC are predictive of outcome, and therefore separate enumeration of intact CTC and apoptotic CTC is useful in tailoring systemic treatment. 51 Patients with a continuous presence of apoptotic or clustered CTCs in follow-up samples after systemic therapy initiation had worse prognosis than patients without these CTC characteristics. In patients with ≥5 CTC/7.5 mL blood at baseline, morphologic characterization of persistent CTCs could be an important prognostic marker during treatment, in addition to CTC enumeration alone.…”
Section: Breast Cancermentioning
confidence: 94%
“…In addition, apoptotic CTCs are more frequently encountered during follow‐up in dormancy candidate patients who remain disease free compared to those with subsequent late relapse, suggesting that monitoring proliferation and apoptosis in CTCs during clinical dormancy merits further investigation as a tool for predicting late disease recurrence . A recent study has shown that in metastatic breast cancer, intact and apoptotic CTC are predictive of outcome, and therefore separate enumeration of intact CTC and apoptotic CTC is useful in tailoring systemic treatment . Patients with a continuous presence of apoptotic or clustered CTCs in follow‐up samples after systemic therapy initiation had worse prognosis than patients without these CTC characteristics.…”
Section: Circulating Tumor Cellsmentioning
confidence: 99%